Analysis of Customer Service Quality in Overseas Shipping in Increasing Customer Satisfaction of PT. Pos Indonesia Persero KCU 60000 Surabaya - Qori Nur Rizka; Elok Vilantika (LP2M IAIN Palopo, 2026)
In service marketing management, service quality is a key determinant of competitive advantage. This study analyzes the performance of Customer Service (CS) in handling international shipments at PT. Pos Indonesia (Persero) KCU 60000 Surabaya. Using a descriptive qualitative method through participant observation from July to December 2025, this study evaluates service gaps that occur in the field. The results show that although shipping volumes are stable, there is an increasing trend of customer complaints due to goods being held at Customs. The analysis identifies the root of the problem as a competency gap among officers in understanding export regulations and weak document verification procedures at the initial point of interaction. This failure to provide assurance has a fatal impact on customer trust and satisfaction. As a strategic solution, this study recommends a relationship marketing approach through: holding intensive